Parents as Promoters of Language Development in Premature Babies: a Proposal for Early intervention - Calderón-Carrillo, Melissa (2018)
Any program of intervention can benefit from the participation of parents. It is necessary to give parents information about what they can do to stimulate the language of their children. This paper aimed to train parents on what to expect in the language development of children, and to teach them techniques of stimulation with the purpose of preventing negative consequences in language development. The sample consisted of 21 premature babies. It was found that, after the training, the parents felt more confident in facilitating the language of their children. The children’s language abilities at 12 months and 36 months were tested. The children obtained typical scores. It was concluded that parents are good promoters of language development in premature babies.